PENGARUH VIRAL MARKETING, CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN DI DISTRO RMBL - Kristanto, Okta Dwi; Indraningrat, Ketut; Prasetiyaningtiyas, Susanti (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: Generally the purpose of this study was to determine the influence of viral marketing, celebrity endorser and brand image against consumer buying decisions in Distro RMBL. The population in this research was the whole followers of Distro RMBL’s instagram account and the total sample of this research was 110 respondents. The independent variables were viral marketing, celebrity endorser and brand image whereas the dependent variable in this research was consumer buying decisions and this research measured by using multiple linear regression analysis. This research’s result indicated that viral marketing, celebrity endorser and brand image influent positively and significantly to consumer buying decisions simultantly. Partially, viral marketing influent consumer buying decisions positively and significantly, celebrity endorser influent consumer buying decisions positively and significantly and also brand image influent consumer buying decisions positively and significantly.Keywords: Viral Marketing, Celebrity Endorser and Brand Image